Unit roots and structural breaks: new knowledge for the ASEAN macroeconomic time series model / Tan Yan Ling … [et al.] - Tan Yan Ling (Research Management Institute (RMI), 2013)
The purpose of this study is to carry out a comprehensive examination of the univariate statistical properties in ASEAN macroeconomic time series from 1960 to 2010 using a battery of endogenous break ADF-type unit root tests. Our empirical findings show that number of rejections of a unit root null is relatively higher when considering structural breaks than without breaks in the models. Most index and rate variables can be treated as trend-stationary processes in Indonesia and Malaysia particularly. However, macroeconomic time series under US Dollar and Local currency terms have an opposite findings. As in ZA models, the US Dollar terms denomination series are more favorable of trendstationary processes. Alternatively, the series under Local Currency terms tend to reject the null hypothesis of a unit root for all ASEAN countries except Thailand in LP models. Hence, the shocks to macroeconomic time series are temporary, these series will return to their long run trend rate of growth. Moreover, the break points are closely associated with global economic events such as the first oil shock of 1973-1975, the second oil shock in 1979-1980, the commodity crisis in 1985-1986 and the Asian financial crisis of 1997-1998. To this extent, if the shocks to series are transitory, then the macroeconomic stabilization policies may not be over-implemented in ASEAN countries particularly for index and rate variables in Indonesia and Malaysia. The policy authorities may use the historical information to forecast future movements in macroeconomic time series. Lastly, our findings also shed light on the importance of considering exchange rate fluctuations in the process of trendstationary and random walk processes.